Studi Pemantauan Kampanye Digital para Kandidat dalam Pilkada 2020 Kabupaten Bantul di Tengah Pandemi Covid-19 - Muhammad Iqbal Khatami; Moch Edward Trias Pahlevi; Azka Abdi Amrurobbi (Jurnal Adhyasta Pemilu, 2021)
Holding regional head elections during a pandemic presents many challenges for the Indonesian people in holding a democratic party. This is due to the implementation of the 2020 Pilkada during the Covid-19 pandemic with the threat of a dangerous virus that can kill humans. This research was conducted in the momentum of monitoring the elections during the Covid-19 pandemic with a focus on the campaign stages in the Bantul Regency. This study uses mixed methods with two data collection techniques: surveys and Nvivo-12 Plus software. The results of this study are: First, Facebook is the best social media for obtaining campaign materials from candidate pairs in the Bantul Pilkada. Second, social media is considered adequate as a political campaign platform if balanced with conventional campaigns. Third, most voters in Bantul Regency who use Facebook have never commented on the campaign of candidate pairs in the Pilkada of the Bantul Regency. Fourth, some issues have almost similar tendencies between candidate pairs, namely discussing social & culture and religion & tolerance. Fifth, Halim-Joko is considered successful in delivering campaign materials through content on social media compared to Suharsono-Totok. Sixth, the public's response tends to be neutral in responding to campaign issues on social media.